Implementasi Pembelajaran Sejarah Kebudayaan Islam berbasis Kurikulum Merdeka di MTS Al-Ihya Tanjung Gading Kabupaten Batu Bara - Rhada Clesya Chanan Khan; Khairuddin Lubis; Dewi Sundari (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2025)
Islamic Cultural History (ICH) learning in madrasahs faces challenges in adapting to the Independent Curriculum, particularly in transforming teacher-centered historical instruction into more contextual and student-centered learning. This study aims to describe the implementation of Islamic Cultural History (ISC) learning based on the Independent Curriculum and student responses to its implementation at MTs Al-Ihya Tanjung Gading, Batu Bara Regency. This study uses a qualitative approach with a descriptive research type. The research subjects included ISC subject teachers, the principal, and students of MTs Al-Ihya Tanjung Gading. Data collection techniques were carried out through observation, interviews, and documentation, while data validity was tested using source and technique triangulation. Data analysis was conducted through the stages of data reduction, data presentation, and conclusion drawing. The results show that the implementation of the Independent Curriculum in ISC learning provides opportunities for teachers to apply more contextual and student-centered learning strategies. Student responses were generally positive, as reflected in increased learning motivation, active participation in discussions and projects, and greater courage in expressing opinions during the learning process. However, the implementation still faces several obstacles, including limited learning time and differences in students’ abilities to learn independently. Overall, the findings indicate that the implementation of the Independent Curriculum encourages more active student involvement and supports a more interactive learning environment in ISC classes